Myosin IIA-related Actomyosin Contractility Mediates Oxidative Stress-induced Neuronal Apoptosis - Wang, Yan; Xu, Yingqiong; Liu, Qian; Zhang, Yuanyuan; Gao, Zhen; Yin, Mingzhu; Jiang, Nan; Cao, Guosheng; Yu, Boyang; Cao, Zhengyu; Kou, Junping (Frontiers in Molecular Neuroscience, 2017)
Oxidative stress-induced neuronal apoptosis plays an important role in the progression of central nervous system (CNS) diseases. In our study, when neuronal cells were exposed to hydrogen peroxide (H2O2), an exogenous oxidant, cell apoptosis was observed with typical morphological changes including membrane blebbing, neurite retraction and cell contraction. The actomyosin system is considered to be responsible for the morphological changes, but how exactly it regulates oxidative stress-induced neuronal apoptosis and the distinctive functions of different myosin II isoforms remain unclear. We demonstrate that myosin IIA was required for neuronal contraction, while myosin IIB was required for neuronal outgrowth in normal conditions. During H2O2-induced neuronal apoptosis, myosin IIA, rather than IIB, interacted with actin filaments to generate contractile forces that leaded to morphological changes. Moreover, myosin IIA knockout using CRISPR/Cas9 reduced H2O2-induced neuronal apoptosis and the associated morphological changes. We further demonstrate that caspase-3/Rho kinase 1 (ROCK1) dependent phosphorylation of myosin light chain (MLC) was required for the formation of the myosin IIA-actin complex. Meanwhile, either inhibition of myosin II ATPase with blebbistatin or knockdown of myosin IIA with siRNA reversely attenuated caspase-3 activation, suggesting a positive feedback loop during oxidative stress-induced apoptosis. Based on our observation, myosin IIA-actin complex contributes to actomyosin contractility and is associated with the positive feedback loop of caspase-3/ROCK1/MLC pathway. This study unravels the biochemical and mechanistic mechanisms during oxidative stress-induced neuronal apoptosis and may be applicable for the development of therapies for CNS diseases.